A Survey of Ismaili Studies Part 2: Post‐Fatimid and Modern Ismailism. Issue 11 (November 2016) - Andani, Khalil
Abstract: This article continues to discuss the major scholarly issues and developments in the study of Ismaili Muslim history and thought in the post‐Fatimid and modern periods. In general, scholarly coverage of the Nizari Ismailis greatly outweighs that of the Tayyibis. Following the concealment of the Tayyibi Imams in the 12th century, the Tayyibi da'wah continued in Yemen under the leadership of da'is representing the Imams and divided into two major groups – the Sulaymanis and Da'udis. The Nizari Imamat continued in Persia until the public emergence of their recent living Imams, the Aga Khans, in modern times. The scholarly issues and themes discussed in this article include the establishment of the Tayyibi da'wah, later Tayyibi cosmology, the 1164 Nizari declaration of qiyamah, the survival of Nizari communities in Persia and South Asia after the Mongol invasion, and modern Ismaili leadership institutions and communities. The article concludes by briefly summarizing the state of research for different periods of Ismaili history/thought and proposing some future trajectories for the progress of Ismaili studies.